Measuring menstrual hygiene experience: development and validation of the Menstrual Practice Needs Scale (MPNS-36) in Soroti, Uganda - Hennegan, J; Nansubuga, A; Smith, C; Redshaw, M; Akullo, A; Schwab, KJ (BMJ Publishing Group, 2020)
OBJECTIVE:This study describes the development and validation of the Menstrual Practice Needs Scale (MPNS-36), which measures the extent to which respondents' menstrual practices and environments meet their needs. METHODS:A 54-item pool was developed following systematic review of qualitative and quantitative studies and expert feedback. Item reduction and scale validation were undertaken using a cross-sectional survey of 538 menstruating schoolgirls in Soroti, Uganda. Test-retest reliability was assessed in a subsample of 52 girls 2 weeks after the first administration. Construct validity was tested through relationships with hypothesised correlates: confidence to manage menses, self-reported school absenteeism and mental health symptoms. RESULTS:The MPNS-36 comprises 28 items applicable to all respondents and 8 items capturing washing and drying experiences for those reusing menstrual materials. A four-factor solution for the core 28 items was the best fit for the data (root mean square error of approximation (RMSEA)=0.028-0.029; comparative fit index (CFI)=0.961-0.964; Tucker-Lewis index (TLI)=0.953-0.955), supplemented by two factors for reuse (RMSEA=0.021-0.030; CFI=0.987-0.994; TLI=0.981-0.991). Subscale and total scores were calculated as mean scores to support accessibility for practitioners. The subscales were 'material and home environment needs' (11 items, αordinal=0.84), 'transport and school environment needs' (5 items, αordinal=0.73), 'material reliability concerns' (3 items, αordinal=0.55), 'change and disposal insecurity' (9 items, αordinal=0.80), 'reuse needs' (5 items, αordinal=0.76) and 'reuse insecurity' (3 items, αordinal=0.56). Relationships between subscales and hypothesised correlates supported validity. Home-based and school-based items were more strongly associated with confidence to manage menstruation at home and school, respectively. Higher total scores indicated more positive experiences and were associated with greater odds of not missing school during the last menstrual period (OR=2.62, 95% CI 1.52 to 4.50). Test-retest reliability was moderate (total score: intraclass correlation coefficient, ICC(2,1)=0.69). CONCLUSIONS:The MPNS-36 demonstrated acceptable reliability and validity. It is the first measure to capture perceived menstrual hygiene and may be useful across a range of study designs. Future research should explore the validity and suitability of the measure across contexts and populations.